A magyar „Fiume és Adria kutatás" néhány történeti aspektusa, különös tekintettel Havass Rezső munkásságára - Bali, Lóránt; Pap, Norbert (Közép-Európai Közlemények, 2014)
Within the Austro-Hungarian monarchy, the creation of a permanent Hungarian hinterland was included among our most important geopolitical ambitions. After the Compromise, the Hungarian scientific life recognized the significance of this in a short period of time. One of the main propagator of these efforts was Rezsı Havass. Hungarian intellectuals involved in the ‘regionalism’ research between the two world wars also supported the idea. The greatness of Havass was due to the fact that he was also able to recognize the situation and possibilities of our country in the global geographical space. He knew also what effects the opening of the Suez Canal would assess on the positions of Fiume. He regarded the creation of the right hinterland as essential and to widen the already existing ones. The main means of was seen in the broadening of the railway network. The sea exit access of Hungary was linked to the extension of the Hungarian geopolitical space over to the Balkan peninsula. In the person of Rezsı Havass we could respect a true “monarchiéer”.